BURDEN OF FAMILY CAREGIVER - Faida Annisa (Belitung Raya Foundation, Indonesia, 2016)
Shifting from hospital-based care to community-based care involves the family as advanced caregivers to the patients with schizophrenia at their home. Yet, they have need of knowledge and skill in caring the patients as well as support from health care providers and society. Family caregivers should be well-prepared to take care the patients with schizophrenia at home since it gets some negative consequences on their physical, psychological, social, and financial. Nurse needs to assess the factors that might influence the family caregivers to feel burden, and include the family caregivers into nursing care in which would not only to improve the patients’ mental health but also the family caregivers.